Resistência à fratura de coroas cerâmicas monolíticas fabricadas em CAD/CAM cimentadas sobre diferentes pilares de implante - Meneghetti, Priscila Ceolin (2019)
Objective: to evaluate the fracture strength of monolithic ceramic unit crowns with different thickness and cemented on solid abutment and tiBase. The hypotheses presented are that (i) the presence of the fixing screw hole decreases the crown fracture strength, (ii) the restoring material influences the fracture resistance, (iii) the restoration thickness influences the fracture resistance of the restorations. Materials and methods: A total of 64 upper second premolar crowns were made for the solid abutment and Variobase C® abutment over the implant analog Straumann Tissue Level. The crowns were made of lithium dissilicate (IPS e.max CAD) and zirconia (Incoris ZI) with 0,5 mm and 1,5 mm thickness in the occlusal, and divided into 8 groups (n = 8): SE05, SE15, SZ05, SZ15, VE05, VE15, VZ05, VZ15. The crowns were cemented with resin cement and the screw access restored with composite resin. After mechanical cycling, the specimens were submitted to the test of fracture resistance in the universal test machine and the maximum force recorded in Newtons (N). The results were submitted to the Shapiro-Wilk test followed by 3-way ANOVA and Tukey (a= 5%). Results: SZ15: 5368,6 N ± 536,74 A; SZ05: 4809,8 N ± 857,55 A; SE15: 2068,8 N ± 359,77 B; SE05: 1887,4N ± 276,94 B; VZ15: 1935,5N ± 274,51 B; VZ05: 1759,4 N ± 334,34 B; VE15: 963,5 N ± 198,92 C; VE05: 924,8 N ± 152,01 C. Conclusions: The presence of the screw access channel reduced in half the fracture strength of the crowns when compared to the crowns cemented on a solid abutment. Incoris ZI showed higher fracture resistance than the IPS e.max CAD independent of the abutment and thickness. The different thicknesses of the restorations had little influence on fracture resistance.